On the Social Optimality of the Value Maximization Criterion - Lee, Wayne Y.; Senchak, Andrew J. (Journal of Financial and Quantitative Analysis, 1980)
As an operational objective for firm management, the market value maximization criterion derives its theoretical validity from the Fisherian separation principle which states that production decisions for an economy can be made without regard to consumer-investors' preferences for consumption, given perfectly competitive markets. In other words, if the firm's activities do not affect the prices of consumptive goods, then maximizing the wealth of its shareholders will lead to a maximization of each shareholder's utility. Not only does this optimality criterion avoid the ambiguities and vagaries of constructing an aggregate shareholder preference function, but when implemented as a firm decision rule, should result in the same production plan that each investor would select himself, and thereby should represent a Pareto optimal allocation of resources: (Hirshleifer [5, Chapters 1, 9]; Fama and Miller [3, Chapters 2, 7]; and more recently, Ekern and Wilson [2], Merton-Subrahmanyam [7], LeRoy [6]).